2016
DOI: 10.1159/000444676
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>TPH1</i></b> and <b><i>5-HTTLPR</i></b> Genes Specifically Interact in Opiate Dependence but Not in Alcohol Dependence

Abstract: Background: Different drug dependencies may have unique genetic vulnerabilities. Changes in serotonin availability and function have been linked to addiction. We investigated whether 2 serotonergic polymorphisms, TPH1 A218C (rs1800532) and 5-HTT-linked promoter region (5-HTTLPR) (rs25531), are differently associated with alcohol or opiate dependence. Methods: Alcohol-dependent patients (n = 292), opiate-dependent patients (n = 309), and healthy controls (n = 301) were recruited from the Han Chinese population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Although heterogeneity test of the included studies did not show significant difference in their effect sizes, ethnic difference may cause a differential distribution of genetic polymorphisms, evidenced by a significant increase in the L allele in the controls of three studies with Caucasian subjects21,28,29 than that in the others25,27,32 (56.8% vs 38.6%, P <0.001). So, the association of the 5-httlpr polymorphism with HD was also examined separately in studies with Caucasian and non-Caucasian subjects.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Although heterogeneity test of the included studies did not show significant difference in their effect sizes, ethnic difference may cause a differential distribution of genetic polymorphisms, evidenced by a significant increase in the L allele in the controls of three studies with Caucasian subjects21,28,29 than that in the others25,27,32 (56.8% vs 38.6%, P <0.001). So, the association of the 5-httlpr polymorphism with HD was also examined separately in studies with Caucasian and non-Caucasian subjects.…”
Section: Resultsmentioning
confidence: 73%
“…Six studies, with 2,459 subjects (868 patients and 1,591 controls), were included into the analysis (Table 1). While only two studies showed a significant association of the S allele with HD, 21,32 other studies showed no association (Figure 1A). The homogeneity analysis showed a negative result ( χ 2 =4.72, df =5, P =0.451), which suggested that the effect sizes from individual studies were not statistically different and justified the use of fixed effects model.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation